A constrained total least squares calibration method for distributed microphone array. (November 2018) - Wang, Rong; Chen, Zhe; Yin, Fuliang
Abstract: Microphone positions have to be calibrated in distributed microphone array applications. A constrained total least squares calibration method for distributed microphone arrays is proposed in this paper. All the source event positions are first estimated by the weighted multidimensional scaling algorithm. Then the suitable source events are picked up by the TDOA selection strategy at each node. Finally, the node microphones are calibrated by the total least squares, and further refined based on constrained total least squares when the estimated results suffer from large errors. The proposed method can obtain higher calibration accuracy and works well in noise and reverberation conditions. Simulation and real-world experiment results reveal the validity of the proposed method.